KONSTRIBUSI MODEL TADZKIRAH DALAM PENGAJARAN DAN PEMBELAJARAN BAHASA INGGRIS BERKARAKTER PADA ANAK USIA DINI - Widhiya Ninsiana (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
Character education for early childhood is highly recommended it. Early childhood is a golden age for children, that is 0-8 age. Tadzkirah model is a learning character model is derived from the theory of Islamic education. Tadzkirah abbreviation is exemplary, guidance, motivation, honesty, continuity, remind, repetition, organization, heart. Tadzkirah models are applied in teaching English character for early childhood, which is packaged in a game. English game character, such as, singing, storytelling, and games in early childhood provides a positive contribution in the development of childhood character, namely courtesy, responsibility, diligence, respect, sincerity.